2015
DOI: 10.1016/j.mce.2015.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Production, purification, and characterization of recombinant hFSH glycoforms for functional studies

Abstract: Summary Previously, our laboratory demonstrated the existence of a β-subunit glycosylation-deficient human FSH glycoform, hFSH21. A third variant, hFSH18, has recently been detected in FSH glycoforms isolated from purified pituitary hLH preparations. Human FSH21 abundance in individual female pituitaries progressively decreased with increasing age. Hypo-glycosylated glycoform preparations are significantly more active than fully-glycosylated hFSH preparations. The purpose of this study was to produce, purify a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 38 publications
1
55
0
Order By: Relevance
“…The present study used purified recombinant hFSH glycoforms, FSH 21/18 and FSH 24 , and the KGN human granulosa cell line as our model system. Analysis of the GH 3 cell-derived FSH glycoforms revealed oligosaccharides similar to those present in pituitary FSH glycoforms (13). Hypo-glycosylated hFSH 21/18 glycoforms exhibited significantly greater ability to stimulate cAMP and PKA-dependent signaling as compared to fully-glycosylated FSH 24 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The present study used purified recombinant hFSH glycoforms, FSH 21/18 and FSH 24 , and the KGN human granulosa cell line as our model system. Analysis of the GH 3 cell-derived FSH glycoforms revealed oligosaccharides similar to those present in pituitary FSH glycoforms (13). Hypo-glycosylated hFSH 21/18 glycoforms exhibited significantly greater ability to stimulate cAMP and PKA-dependent signaling as compared to fully-glycosylated FSH 24 .…”
Section: Discussionmentioning
confidence: 88%
“…The greater ability of FSH 21/18 to activate cellular signaling is presumptively due, at least in part, to a greater affinity of FSH 21/18 vs FSH 24 for the FSHR (9, 13). Studies using rat or bovine testis homogenates or CHO cells stably expressing the human FSHR clearly demonstrated that FSH 21/18 occupied more FSH binding sites than FSH 24 (9,13). The relative ability of FSH glycoforms to bind the FSHR was not affected by the numbers of FSHR present in the ligand-binding assay, since testis homogenates and CHO cells, which overexpress the FSHR, represent conditions of low vs high receptor density, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). The purification and characterization of the hormones from GH 3 -conditioned media were described in detail elsewhere [6, 17, 18]. Western blot analysis of FSH preparations was performed with the FSHβ subunit-specific primary antibody RFSH20 (1:5000) that detected two bands corresponding to 18 KDa and 21 KDa in the FSH 21/18 preparation (Fig.1B, Lane 1), and a single band at 24KDa in the case of FSH 24 and hFSH AFP 7298 reference preparation (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It was predicted that such age-related FSH glycoforms act differently in different target cells [4, 14, 17]. Direct purification of FSH glycoforms from human pituitaries and/or urine collected at different ages and their characterization indeed identified hypo-glycosylated FSH is a mixture of FSH 18 and FSH 21 glycoforms present as the dominant form in young age and fully-glycosylated FSH, designated as FSH 24 is the dominant form in old age [4, 6, 14, 17-20]. Recombinant expression in a heterologous GH 3 cell culture system followed by purification and biochemical characterization revealed that these FSH glycoforms differ in the number or location of N-linked glycan chains on FSHβ subunit [4-7, 14].…”
Section: Introductionmentioning
confidence: 99%